2017
DOI: 10.1016/j.celrep.2017.05.040
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-Mediated Dynamic Bidirectional Shift between the Subclasses of Glioblastoma Stem-like Cells

Abstract: Summary Large scale transcriptomic profiling of glioblastoma (GBM) into subtypes has provided remarkable insight about the pathobiology and heterogeneous nature of this disease. The mechanisms of speciation and inter-subtype transitions of these molecular subtypes require better characterization to facilitate the development of subtype-specific targeting strategies. The deregulation of microRNA expression among GBM subtypes, and their subtype-specific targeting mechanisms are poorly understood. To reveal the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 30 publications
(47 reference statements)
1
35
0
Order By: Relevance
“…Gene expression-based tumor subtypes have been resolved to sample-specific mixtures of up to 4 dominant single-cell GBM expression signatures with unique underlying functional cell states that are governed by genetic and microenvironmental cues, but appear to be both plastic and commutable, which is consistent with other similarities to neural precursor cells (Neftel et al, 2019). Studies focused on GSCs identified two distinct functional states that match GBM molecular subtypes Wang et al, 2019b), as well as a microRNA (miRNA)-driven, possibly extracellular vesicle (EV)mediated, bidirectional transition between distinct GSC subpopulations within the tumor (Ricklefs et al, 2016;Rooj et al, 2017). Molecular profiles of GSC-EVs suggest that their effects within the tumor may depend on the molecular subtype and functional state of the donor cells (Spinelli et al, 2018;Wei et al, 2017).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Gene expression-based tumor subtypes have been resolved to sample-specific mixtures of up to 4 dominant single-cell GBM expression signatures with unique underlying functional cell states that are governed by genetic and microenvironmental cues, but appear to be both plastic and commutable, which is consistent with other similarities to neural precursor cells (Neftel et al, 2019). Studies focused on GSCs identified two distinct functional states that match GBM molecular subtypes Wang et al, 2019b), as well as a microRNA (miRNA)-driven, possibly extracellular vesicle (EV)mediated, bidirectional transition between distinct GSC subpopulations within the tumor (Ricklefs et al, 2016;Rooj et al, 2017). Molecular profiles of GSC-EVs suggest that their effects within the tumor may depend on the molecular subtype and functional state of the donor cells (Spinelli et al, 2018;Wei et al, 2017).…”
Section: Introductionsupporting
confidence: 53%
“…Extensive molecular profiling of GBM tissues (Freije et al, 2004;Phillips et al, 2006;Verhaak et al, 2010), single cells (Patel et al, 2014;Rooj et al, 2017;Neftel et al, 2019;Ricklefs et al, 2016;Wang et al, 2019b), and secreted nanoparticles (Ricklefs et al, 2016;Wei et al, 2017;Spinelli et al, 2018;Zhang et al, 2019b) has driven recent developments in the identification of GBM tumor subtypes that support a coherent model of GBM heterogeneity. Gene expression-based tumor subtypes have been resolved to sample-specific mixtures of up to 4 dominant single-cell GBM expression signatures with unique underlying functional cell states that are governed by genetic and microenvironmental cues, but appear to be both plastic and commutable, which is consistent with other similarities to neural precursor cells (Neftel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The major therapeutic advantage of miRNAs arises from the fact that a single miRNA can target multiple genes involved in distinct cellular functions. For example, increasing the expression of a tumour-suppressor miRNA (ts-miRNA) like miR-128-3p [11][12][13][14][15][16][17] or miR-145-5p [18][19][20][21][22][23] in GBM can block cell proliferation, self-renewal, invasion, metastasis, angiogenesis and drug resistance by selectively down-regulating the expression of multiple genes, Figure-2. Similarly, repeated systemic treatment with miR-138 blocks multiple key immune-checkpoints proteins in T-cells (CTLA-4, PD-1 and FoxP3), resulting in significant Tcell mediated tumour regression and increased survival in orthotropic brain-tumour model expressing PD-L1 ligand [24].…”
Section: Microrna Therapeutics For Glioblastomamentioning
confidence: 99%
“…There exists an inverse correlation between miR-128 expression and grade of glioma [11]. MiR-128 reduces tumour growth (EGFR, PDGFR [12]), stemness (BMI1 and E2F3 [13,14]), invasion (DCX, RELN [15]), induces apoptosis [16] and senescence [17]. miR-128 was expressed at low levels in proneural-GSCs (Glioma Stem-like Cancer cells) and no expression in more aggressive mesenchymal-GSCs [14].…”
Section: Table -1 Mirna and Gbmmentioning
confidence: 99%
“…This was reflected in highly heterogeneous profile of miRNA expression in GBM subtypes (88). Moreover, it was reported that the expression of the subtype-enriched miRNAs such as miR-128 within transcriptionally and phenotypically diverse subpopulations of patientderived GSCs is a potent mechanism of bidirectional transitions between GBM subpopulations (89). This could consequently result in intermediate hybrid stages, highlighting highly intricate intra-tumoral networking.…”
Section: Networking Between Stem-like Cells' Subpopulations: Heterogementioning
confidence: 99%